2016
DOI: 10.1007/s10493-016-0091-9
|View full text |Cite
|
Sign up to set email alerts
|

Species composition, distribution, ecological preference and host association of ticks in Cyprus

Abstract: Tick population and species depend on the effect of biotic and abiotic factors, especially vegetation, climate and host density; Cyprus, due to the mild climate, favors the appearance and spread of tick-borne infections. Our objective was to identify the tick species present in the island, to investigate their geographical distribution and their epidemiological implications. During a three-year study (2004-2006) we collected ticks from domestic and wild animals over the island of Cyprus. Data on temperature, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…The general spatial distribution of ticks in Italy observed in the present survey is consistent with findings of large-scale studies conducted in Mediterranean countries including Spain [ 9 ], Cyprus [ 13 ] and Greece [ 35 ]. These studies found R. sanguineus group to be the most prevalent tick species, while studies in temperate European countries including the Netherlands [ 36 ], Belgium [ 10 ] and UK [ 12 ] reported a higher prevalence of I. ricinus and I. hexagonus .…”
Section: Discussionsupporting
confidence: 91%
“…The general spatial distribution of ticks in Italy observed in the present survey is consistent with findings of large-scale studies conducted in Mediterranean countries including Spain [ 9 ], Cyprus [ 13 ] and Greece [ 35 ]. These studies found R. sanguineus group to be the most prevalent tick species, while studies in temperate European countries including the Netherlands [ 36 ], Belgium [ 10 ] and UK [ 12 ] reported a higher prevalence of I. ricinus and I. hexagonus .…”
Section: Discussionsupporting
confidence: 91%
“…The area of Paphos, Cyprus, may be Lyme disease free as no anti- B . burgdorferi antibodies were detected in any of the dogs tested in this study, and the tick vectors that transmit this pathogen, including Ixodes Ricinus , have not yet been identified in Cyprus [12]. In two dogs (1%) antigens for D .…”
Section: Discussionmentioning
confidence: 99%
“…In Morocco, Morel (2000) revealed that the seasonal dynamic of R. bursa was unimodal, with a peak in activity during the warm season ranging from March to September; this finding is similar to the results of the present study. Likewise, the R. turanicus tick species appears in March and disappears in July (Tsatsaris et al 2016). As shown in Figure 2, R. turanicus has been collected between April and November, with a peak infestation in April and May.…”
Section: Discussionmentioning
confidence: 99%